Implementasi Metode Analytic Hierarchy Process - Weighted Product Untuk Rekomendasi Hunian Ideal (Studi Kasus: Kota Malang) - Rizaldy Aditya Nugraha; Indriati Indriati; Imam Cholissodin (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The purpose of this study is to help prospective house buyers in getting the recommendation for an ideal house to be purchased. Prospective house buyers that were looking for a house of their dreams still found it difficult to obtain the appropriate recommendation suitable with their desires. Therefore, this study was conducted to create a decision support system application of ideal house recommendation to facilitate a prospective house buyer in obtaining an ideal house recommendation. The input data used on this system is a weight priority measure for each criteria and sub criteria of the house specified by the prospective house buyer. Then these input data are calculated by using analytic hierarchy process - weighted product method. The analytic hierarchy method is used to obtain the criteria and sub criteria weight which is then used for the calculation of weighted product method. The final result of this system is the rank order of ideal house recommendation. The test performed on this system is done on the pairwise comparison matrices with 80% accuracy.